Pengaruh Kecepatan Layanan dan Ketersediaan Layanan Digital terhadap Kepuasan Masyarakat di BPKAD Kota Yogyakarta - Perdana, Mahendra Jati Putra; Prasetyo, Heri (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In the digital era, public expectations for fast and accessible services have increased significantly. However, the implementation of digital services in government institutions often encounters challenges such as low digital literacy and concerns over data security. This study aims to examine the effect of service speed and digital service availability on community satisfaction in the Regional Financial and Asset Management Agency (BPKAD) of Yogyakarta City. Using a quantitative research approach, data were collected through questionnaires distributed to 109 service users, selected through simple random sampling. The instrument was developed based on validated theoretical indicators and analyzed using SPSS version 25. The analytical techniques included validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. The results show that both service speed and digital service availability have a significant positive effect on community satisfaction, both partially and simultaneously. Specifically, digital service availability covering accessibility, system security, reliability, and uptime shows a stronger influence compared to service speed. These findings support the Technology Acceptance Model (TAM), highlighting the importance of perceived usefulness and ease of use in shaping user satisfaction. This study provides empirical evidence for local governments to integrate fast conventional service with user-centered digital innovations, particularly within the framework of smart city governance.